Effects of age and pasture type on the concentration and prevalence of tetracycline and macrolide resistant Enterococcus species in beef cow-calf production system - Agga, Getahun E.; Galloway, Hunter O.; Netthisinghe, Annesly M. P. (Frontiers in Antibiotics, 2022)
Enterococci are a normal flora of the gastrointestinal tracts of humans and animals. Enterococci can also cause life-threatening nosocomial infections. Antimicrobial-resistant Enterococcus species have been reported in the feedlot and dairy cattle productions and in meat and milk products, suggesting their foodborne importance. Cow-calf operations represent a significant segment in the beef production system by producing weaned calves. Weaned calves are brought into the feedlot to be finished for meat, and culled cows are also slaughtered for beef, primarily for ground beef products. Infection dynamics in the cow-calf operation can contribute to meat contamination. This study evaluated the effects of age and wheat grazing on the concentration and prevalence of a macrolide antibiotic erythromycin (ERYr) and tetracycline (TETr) resistant enterococci, associated resistance genes and species distribution in a cow-calf production system. In 2017 and 2018, 32 Angus breed cow-calf pairs were randomly assigned to feed on tall fescue or wheat pasture in two independent field experiments. During the grazing experiments of 2-3 weeks, fecal samples were collected weekly and cultured to enumerate, isolate and identify ERYr, TETr, and generic enterococci, using media supplemented with erythromycin, tetracycline or non-supplemented media, respectively. The two main species frequently associated with human illnesses, Enterococcus faecium and E. faecalis, were widely distributed in the cow-calf groups. Generic and TETr- enterococci were prevalent (96-100% prevalence) and abundant (3.2-4.9 log10 CFU/g) in the cow-calf population; however, ERYr enterococci were enumerable by direct plating only from a single cow despite being detected in at least 40% of the fecal samples after enrichment, showing their low abundance. TET- and ERY-resistance were mainly conferred by tet(M) and erm(B), respectively. Wheat grazing reduced the concentration of TETr enterococci and modified enterococcal species and resistance gene distributions. Hence, it is necessary to further investigate wheat grazing in cow-calf production as a potential strategy to mitigate antimicrobial resistance.